Measurement of the U-238/U-235 fission cross section ratio at CSNS – Back-n WNS. (1st June 2020) - Wen, Jie; Yang, Yiwei; Wen, Zhongwei; Liu, Rong; Liu, Xingyan; Han, Zijie; Chen, Qiping; Ren, Zhizhou; An, Qi; Bai, Huaiyong; Bao, Jie; Cao, Ping; et al.
Highlights: Measured the 238U/235U fission cross section ratio in 1–20 MeV. The nonuniformity of the neutron beam profile was considered. Experimental uncertainties of 2.3%–3.6% in 1.4–20 MeV while 4.1%–11% in 1–1.4 MeV. Provide information and data support in relevant nuclear data evaluation. Abstract: Based on the China Spallation Neutron Source (CSNS) – Back-streaming white neutron source (Back-n WNS), the measurement of the U-238/U-235 fission cross section ratio in 1–20 MeV neutron energy region has been carried out by a multi-cell fast fission ionization chamber using the time-of-flight method. The measured resonance peaks of the 235 U(n, f) reaction are in good agreement with those of the ENDF/B-8.0 database. The measured six groups of the U-238/U-235 fission cross section ratios in 1–20 MeV neutron energy region agree with those of the ENDF/B-8.0 database in trend, and the average discrepancies between experiment and database are from 1.9% to 2.6%. The relative experimental uncertainties are 2.3%–3.6% (1.4–20 MeV), and the measured data agree with those of database within experimental uncertainties at most energy points. The measured U-238/U-235 fission cross section ratio could provide information and data support in relevant nuclear data evaluation.